Evidence for the Effectiveness of Remdesivir (GS-5734), a Nucleoside-Analog Antiviral Drug in the Inhibition of IK(M) or IK(DR) and in the Stimulation of IMEP - Wei-Ting Chang; Wei-Ting Chang; Wei-Ting Chang; Ping-Yen Liu; Ping-Yen Liu; Zi-Han Gao; Shih-Wei Lee; Wen-Kai Lee; Sheng-Nan Wu; Sheng-Nan Wu; Sheng-Nan Wu (Frontiers Media S.A., 2020)
Remdesivir (RDV, GS-5734), a broad-spectrum antiviral drug in the class of nucleotide analogs, has been particularly tailored for treatment of coronavirus infections. However, to which extent RDV is able to modify various types of membrane ion currents remains largely uncertain. In this study, we hence intended to explore the possible perturbations of RDV on ionic currents endogenous in pituitary GH3 cells and Jurkat T-lymphocytes. The whole-cell current recordings of ours disclosed that upon membrane depolarization in GH3 cells the exposure to RDV concentration-dependently depressed the peak or late components of IK(DR) elicitation with effective IC50 values of 10.1 or 2.8 μM, respectively; meanwhile, the value of dissociation constant of RDV-induced blockage of IK(DR) on the basis of the first-order reaction was yielded to be 3.04 μM. Upon the existence of RDV, the steady-state inactivation curve of IK(DR) was established in the RDV presence; moreover, the recovery became slowed. However, RDV-induced blockage of IK(DR) failed to be overcome by further addition of either α,β-methylene ATP or cyclopentyl-1,3-dipropylxanthine. The RDV addition also lessened the strength of M-type K+ current with the IC50 value of 2.5 μM. The magnitude of voltage hysteresis of IK(M) elicited by long-lasting triangular ramp pulse was diminished by adding RDV. Membrane electroporation-induced current in response to large hyperpolarization was enhanced, with an EC50 value of 5.8 μM. Likewise, in Jurkat T-lymphocytes, adding RDV declined IK(DR) amplitude concomitantly with the raised rate of current inactivation applied by step depolarization. Therefore, in terms of the RDV molecule, there appears to be an unintended activity of the prodrug on ion channels. Its inhibition of both IK(DR) and IK(M) occurring in a non-genomic fashion might provide additional but important mechanisms through which in vivo cellular functions are seriously perturbed.